Socialization of Awig-Awig Subak Arrangement: Subak Arrangement as a World Cultural Heritage in Subak Pulagan Gianyar - I Gusti Agung Mas Rwa Jayantiari; AA Gede Oka Parwata; Nyoman Mas Aryani; Sagung Putri ME Purwani (Fakultas Hukum, Universitas Warmadewa, 2022)
The purpose of the service is to be able to compile awig-awig, the regulations used in the Subak organization that are the foundation of sustainable environmental development. It is important to be carried out in the context of spatial planning around Subak, therefore it is maintained and there is no easy change of land function that affects the existence of Subak. This service activity was carried out using lecture, discussion and question and answer methods when taking an inventory of the problems faced by Subak Pulagan Gianyar and then making awig-awig arrangements related to spatial planning around Subak. The target focus in the management of Subak is the apparatus of Subak officers and the members of Subak Pulagan Gianyar so that it is expected to have guidelines for the functional customary law community in Bali in determining the rules within the Subak organization. The realization of the service was carried out through reviewing the act of compiling the substance of awig-awig Subak, mainly in the palemahan (environment) section and was warmly welcomed by Subak Pulagan officers. This was responded well because it was realized by the local members of subak that preserving this world’s cultural heritage is the foundation for maintaining their natural environment in a sustainable manner.